2022
DOI: 10.1111/jocs.16918
|View full text |Cite
|
Sign up to set email alerts
|

Aortic remodeling, distal stent‐graft induced new entry and endoleak following frozen elephant trunk: A systematic review and meta‐analysis

Abstract: Background The introduction of the frozen elephant trunk (FET) technique for total arch replacement (TAR) has revolutionized the field of aortovascular surgery. However, although FET yields excellent results, the risk of certain complications requiring secondary intervention remains present, negating its one‐step hybrid advantage over conventional techniques. This systematic review and meta‐analysis sought to evaluate controversies regarding the incidence of FET‐related complications, with a focus on aortic re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 89 publications
(196 reference statements)
0
10
0
Order By: Relevance
“…Interestingly, the authors found no association between dSINE and mid-term survival ( 9 ). A Nakhaei et al meta-analysis ( 15 ) of 5,068 patients found a 2% pooled estimate of dSINE (95% CI: 1–6%, I 2 =78%), and there was no heterogeneity (I 2 =0%) amongst European studies, including those utilising THP and E-Vita stent-grafts. However, the reported incidence across the literature was found to be up to 28%.…”
Section: Dsinementioning
confidence: 99%
See 2 more Smart Citations
“…Interestingly, the authors found no association between dSINE and mid-term survival ( 9 ). A Nakhaei et al meta-analysis ( 15 ) of 5,068 patients found a 2% pooled estimate of dSINE (95% CI: 1–6%, I 2 =78%), and there was no heterogeneity (I 2 =0%) amongst European studies, including those utilising THP and E-Vita stent-grafts. However, the reported incidence across the literature was found to be up to 28%.…”
Section: Dsinementioning
confidence: 99%
“…Upon exploring further meta-analyses, across 85 studies encompassing 10,960 patients, Mousavizadeh et al found that the pooled estimate of in-hospital mortality (in 5,569 patients), 30-day mortality (in 6,614 patients), and 1-year mortality (in 1,006 patients) was 7% (95% CI: 5–9%; I 2 =76%), 8% (95% CI: 6–10%; I 2 =76%) and 9% (95% CI: 4–17%; I 2 =90%), respectively ( 23 ). Lastly, a meta-analysis by Nakhaei et al of 5,068 FET patients, reported a relatively lower 5% pooled estimate of in-hospital mortality (95% CI: 4–7%, I 2 =52%) ( 15 ).…”
Section: Mortality and Survivalmentioning
confidence: 99%
See 1 more Smart Citation
“…1 The preservation of false lumen patency due to endoleak is one of the major causes of reoperations in long-term follow-up. 2,3 Although type II endoleak rarely leads to reoperation on the distal aorta, in some cases it can cause negative aortic remodeling and require reintervention. 4 We present a case of type II endoleak treatment using minimally invasive thoracoscopic clipping of an intercostal artery in a patient with negative aortic remodeling after the FET procedure.…”
Section: Introductionmentioning
confidence: 99%
“…[4] However, AD survivors still face many challenges, such as postoperative complications, impairment of physical function, decreased quality of life, and psychological trauma. [5][6][7][8] Therefore, the health promotion of AD is one of the important means to help them recover from the disease.…”
Section: Introductionmentioning
confidence: 99%